The performance of a 22 GHz radio telescope - Gaylard, Michael John (Rhodes University, Faculty of Science, Department of Physics, 1977)
The performance of the Rhodes 22 GHz radio telescope and its improvement are discussed in this thesis. The reflector surfaces of the Cassegrain antenna were surveyed and the surface errors minimised, while the magnitude of thermal and gravitational defomations was calculated. The design and operation of the microwave front end has been improved, and the mixer performance characterised. The continuum and spectral line receivers and their sensitivity are described. The aperture efficiency, which has been raised from 0,47 to 0,57, was deduced from solar and lunar observations and atmospheric attenuation measurements. The antenna beam pattern was also obtained from the observations, with the aid of a computer program, and is compared to that predicted for the telescope.
Keywords: Radio telescopes; Paraboloid